Roe : the history of a national obsession - Ziegler, Mary, 1982- (Yale University Press, 2023)
"Over its half-century of public life, Roe v. Wade took on meanings that extended far beyond its original purpose of protecting the privacy of the doctor-patient relationship. At various times, it forced us to confront hard questions about judicial activism and restraint, the believability of science, racial justice, the suppression of religion, and much more. Mary Ziegler explores the transformations of meaning that have kept abortion on the front lines of our political and social battles"--